UV-B Radiation Induces Root Bending Through the Flavonoid-Mediated Auxin Pathway in Arabidopsis - Wan, Jinpeng; Zhang, Ping; Wang, Ruling; Sun, Liangliang; Wang, Wenying; Zhou, Huakun; Xu, Jin (Frontiers in Plant Science, 2018)
Ultraviolet (UV)-B radiation-induced root bending has been reported; however, the underlying mechanisms largely remain unclear. Here, we investigate whether and how auxin and flavonoids are involved in UV-B radiation-induced root bending in Arabidopsis using physiological, pharmacological, and genetic approaches. UV-B radiation modulated the direction of root growth by decreasing IAA biosynthesis and affecting auxin distribution in the root tips, where reduced auxin accumulation and asymmetric auxin distribution were observed. UV-B radiation increased the distribution of auxin on the nonradiated side of the root tips, promoting growth and causing root bending. Further analysis indicated that UV-B induced an asymmetric accumulation of flavonoids; this pathway is involved in modulating the accumulation and asymmetric distribution of auxin in root tips and the subsequent redirection of root growth by altering the distribution of auxin carriers in response to UV-B radiation. Taken together, our results indicate that UV-B radiation-induced root bending occurred through a flavonoid-mediated phototropic response to UV-B radiation.